The double burden of malnutrition: Further perspective: Authors' reply - Hawkes, Corinna; Ruel, Marie T.; Wells, Jonathan C.; Popkin, Barry M.; Branca, Francesco (Elsevier, 2020)
We thank Saskia Osendarp and colleagues, Mohammad Sorowar Hossain and colleagues, and Christine Stewart and colleagues for their responses to the Lancet Series on the double burden of malnutrition. They make some relevant points that we would like to address here.